Transcriptome analysis identifies TODL as a novel lncRNA associated with proliferation, differentiation, and tumorigenesis in liposarcoma through FOXM1. (November 2022) - Kanojia, Deepika; Kirtonia, Anuradha; Srujana, Namburi Sai Valli; Jeevanandan, Sree Priyanka; Shyamsunder, Pavithra; Sampath, Shruthi Sanjitha; Dakle, Pushkar; Mayakonda, Anand; Kaur, Harvinder; Yanyi, Jiang; Koeffler, H.Phillip; Garg, Manoj
Abstract: Liposarcoma, the most common soft tissue sarcoma, is a group of fat cell mesenchymal tumors with different histological subtypes. The dysregulation of long non-coding RNAs (lncRNAs) has been observed in human cancers including a few studies in sarcoma. However, the global transcriptome analysis and potential role of lncRNAs remain unexplored in liposarcoma. The present investigation uncovers the transcriptomic profile of liposarcoma by RNA sequencing to gain insight into the global transcriptional changes in liposarcoma. Our RNA sequencing analysis has identified that many oncogenic lncRNAs are differentially expressed in different subtypes of liposarcoma including MALAT1, PVT1, SNHG15, LINC00152, and MIR210HG . Importantly, we identified a highly overexpressed, unannotated, and novel lncRNA in dedifferentiated liposarcomas. We have named it TODL, transcript overexpressed in dedifferentiated liposarcoma. TODL lncRNA displayed significantly higher expression in dedifferentiated liposarcoma cell lines and patient samples. Interestingly, functional studies revealed that TODL lncRNA has an oncogenic function in liposarcoma cells by regulating proliferation, cell cycle, apoptosis, differentiation, and tumorigenesis in the murine model. Silencing of TODL lncRNA highlighted the enrichment of several key oncogenic signaling pathways including cell cycle, transcriptional misregulation, FOXM1 network, p53 signaling, PLK1 signaling, FoxO, and signaling Aurora signaling pathways. RNA pull-down assay revealed the binding of TODL lncRNA with FOXM1, an oncogenic transcription factor, and the key regulator of the cell cycle. Silencing of TODL lncRNA also induces adipogenesis in dedifferentiated liposarcomas. Altogether, our finding indicates that TODL could be utilized as a novel, specific diagnostic biomarker, and a pharmacological target for therapeutic development in controlling aggressive and metastatic dedifferentiated liposarcomas. Graphical Abstract: ga1 Highlights: RNA sequencing in different subtypes of liposarcoma identified oncogenic long non-coding RNAs (lncRNAs). Discovered highly overexpressed, novel and unannotated lncRNA in dedifferentiated liposarcomas named as TODL. Functional validation revealed the oncogenic function of TODL novel lncRNA in regulating liposarcoma cell proliferation. TODL LncRNA association with FOXM1 protein stabilizes the latter and regulates liposarcoma progression Silencing of TODL lncRNA induces adipogenesis in dedifferentiated liposarcomas